Contextualized bilingualism among adolescents from four different ethnic groups in Indonesia. (December 2019) - Sari, Betty Tjipta; van de Vijver, Fons J R; Chasiotis, Athanasios; Bender, Michael
Aims and objectives: We were interested in group differences in Indonesia in bilingualism, whether vocabulary knowledge shows a differential pattern across the languages, and whether language skill and usage differences between groups are moderated by contextual factors, such as ethnic group size. Data and analysis: We examined group differences in language usage at home and in public, self-reported proficiency, and vocabulary scores in both languages among 632 adolescents (292 males, Mage = 14.57 years) from four ethnic groups in Indonesia (214 Javanese, 115 Batak Toba, 108 Toraja, and 195 Chinese). Differential item functioning analysis was conducted to test whether adolescents had different vocabulary they only know in one language, which would indicate equality or inequality in access to knowledge in the two languages. Findings: There were large differences in language knowledge and usage. The lowest scores in ethnic language vocabulary and usage were found among the Chinese group. Across groups, scores for Bahasa Indonesia (L2) vocabulary were higher than ethnic language (L1) vocabulary. However, the ranking from easy to difficult words was similar across the languages and there were no specific sets of items that were differentially known in any language. Implication: Despite the differences in bilingualism skill and usage, all groups have similar access to different domains of the languages, and L2 (Bahasa Indonesia) seems to have become the dominant language in all groups. Our findings also imply that bilingualism comprises various domains, including language skill, self-reported proficiency, and self-reported usage, and that the associations between these components are not very strong. Originality: We investigated bilingualism among non-immigrant adolescents in an under-researched, non-WEIRD (western, educated, industrialized, rich, democratic) society. The study shows the role of language usage and skill that is different from a western context in various aspects, such as the dominance of L2 in all groups.